The Relationship of Stress Levels on Menstrual Cycle Disorders in Adolescent Girls - Mayasari, Ade Tyas; Fauziah, Nur Alfi (Universitas Aisyah Pringsewu, 2022)
Menstrual cycle abnormalities are a significant cause of infertility. Ovulation dysfunction accounts for 10-25% of female infertility cases. Data of youth care health services or Pelayanan Kesehatan Peduli Remaja (PKPR) at the Kota Dalam Public Health Center, Pesawaran Regency, in 2020, the number of adolescent girls was 728 people. 11.26% of adolescents have reproductive health problems, namely irregular menstrual cycles. This study aimed to determine the relationship between stress levels and menstrual cycle disorders in adolescent girls in the work area of the Kota Dalam Public Health Center, Pesawaran Regency, in 2021. This type of research was quantitative with an analytic design and cross-sectional approach. The population and sample of all adolescents girls were 38 people with the accidental sampling technique. The data analysis test used in this study used the Chi-Square test.The results showed that the distribution of the frequency of menstrual cycle disorders in adolescent girls, with the category of experiencing menstrual cycle disorders among as many as 18 respondents (47.40%), the distribution of stress frequencies in adolescent girls, with the variety of experiencing stress as many as 22 respondents (57.9%). There was a relationship between stress levels and menstrual cycle disorders in adolescent girls. The results of the analysis were obtained (p-value 0.010 less than 0.05). OR: 8,000. It is suggested that young women can increase their knowledge about menstrual cycle disorders through electronic media or by conducting examinations on health services to avoid complications in menstruation. Teenage girls who experience stress can be overcome by adequate rest, relaxation, regular exercise, recreation, and body massage. Abstrak: Kelainan siklus menstruasi merupakan penyebab infertilitas yang penting. Disfungsi ovulasi berjumlah 10-25% dari kasus infertilitas wanita. Berdasarkan data pelayanan kesehatan peduli remaja (PKPR) di Puskesmas Kota Dalam Kabupaten Pesawaran Tahun 2020, dari 728 orang remaja putri, terdapat sebanyak 11,26% remaja yangmengalami siklus menstruasi yang tidak teratur. Penelitian ini bertujuan untuk mengetahui hubungan tingkat stres terhadap gangguan siklus menstruasi pada remaja putri di wilayah kerja Puskesmas Kota Dalam Kabupaten Pesawaran Tahun 2021. Jenis penelitian kuantitatif dengan desain analitik dan pendekatan cross sectional. Populasi dan sampel seluruh remaja wanita sebanyak 38 orang dengan teknik accidental sampling. Uji analisis data yang digunakan pada penelitian ini menggunakan uji Chi-Square. Hasil penelitian diketahui remaja yang mengalami gangguan siklus menstruasi sebanyak 18 responden (47,40%), yang mengalami sebanyak 22 responden (57,9%). Ada hubungan tingkat stres terhadap gangguan siklus menstruasi pada remaja putri. Hasil analisis diperoleh (p-value 0,010 kurang dari 0,05). OR: 8.000. Disarankan para remaja putri dapat lebih menambah pengetahuannya mengenai gangguan siklus menstruasi melalui media elektronik maupun dengan melakukan pemeriksaan pada pelayanan kesehatan untuk menghindari terjadinya komplikasi pada menstruasi. Remaja putri yang mengalami stres dapat diatasi dengan cara istirahat yang cukup, relaksasi, olahraga teratur, rekreasi, dan pemijatantubuh.